IMPLEMENTASI PEMBELAJARAN QIRAAH SAB’AH DI PONDOK PESANTREN TAHFIDZUL QUR’AN BAITUL ‘ABIDIN DARUSSALAM - isfandiary, suada (ojs.unsiq.ac.id, 2023)
Memorizing and learning the science of the Qur'an is a human effort to protect the validity of the Qur'an. One of them is ¬qira>'a>t Science. In the world of Islamic boarding schools, the phenomenon of Qiraah Sab'ah learning is increasingly showing its existence. Among the many Islamic boarding schools spread across Indonesia, one that studies qira>'a>t is the Tahfiz Islamic Boarding Schoolul Qur'an Baitul 'Abidin Darussalam. The focus of the research in this article is: (1) to find out the recitation techniques that are applied in studying the Qiraah Sab'ah in PPTQ Baitul 'Abidin Darussalam. (2) to find out the factors that hinder and support the study of QiraahSab'ah in PPTQ Baitul 'Abidin Darussalam. In this research, the writer applies a qualitative descriptive method. The descriptive method describes various facts and phenomena of the study of Qiraah Sab'ah in PPTQ Baitul 'Abidin Darussalam. While the author's data collection technique uses observation, interviews, along with supporting books, articles and journals as well as other literature whose discussion is still related as a complement to this research. The results of the research in this article say that the method of studying Qiraah Sab'ah is done by talaqqi/sorogan. The reading of the qira>'a>t is done in jama' kubra>. This learning is effectively carried out at PPTQ BAD because it is supported by flexible time, tutors who master the material, there are halaqoh every month and books with rasm us|mani rules that are familiar to the students. This scientific discipline provides many benefits for the students so that they know more about the various types of Al-Qur'an readings so that Muslims have a high tolerance for differences in Al-Qur'an readings. In practice, there are still obstacles in learning Qiraah Sab'ah, namely the lack of basic understanding from students about Qiraah Sab'ah itself because it still feels foreign which ultimately results in a lack of enthusiasm or enthusiasm for students in learning it.